Temporary ponds and hygrophilous grasslands plant communities in Monfurado Site of Community Importance - Silva, Vasco; Pinto-Cruz, Carla; Espírito-Santo, Maria Dalila (Lazaroa, 2010)
Temporary ponds are seasonal wetlands subjected to extreme and unstable ecological conditions due to the annual alternation between the flooded and dry phases. The ephemeral character of the flora and the changeable annual weather explain why these habitats have been poorly studied and documented. The objective of this study, in the Monfurado Site of Community Importance, was to characterize seasonal wetland plant communities using a phytosociological approach and numerical analysis (classification and ordination). The results lead to the site’s inclusion in two Natura 2000 Network priority habitats: Mediterranean temporary ponds (3170) in depression landform with impermeable layer in the underground with Isoeto-Nanojuncetea vegetation complexes; pseudo-steppe with grasses and annuals of the Thero-Brachypodietea, sub-type ‘Malhadais’ (6220pt2) in shallow areas with Isoeto-Nanojuncetea species.